Microfluidic Synthesis Enables Dense and Uniform Loading of Surfactant‐Free PtSn Nanocrystals on Carbon Supports for Enhanced Ethanol Oxidation. (15th March 2016) - Wu, Fuxiang; Zhang, Dongtang; Peng, Manhua; Yu, Zhihui; Wang, Xiayan; Guo, Guangsheng; Sun, Yugang
Abstract: Developing new synthetic methods for carbon supported catalysts with improved performance is of fundamental importance in advancing proton exchange membrane fuel cell (PEMFC) technology. Continuous‐flow, microfluidic reactions in capillary tube reactors are described, which are capable of synthesizing surfactant‐free, ultrafine PtSn alloyed nanoparticles (NPs) on various carbon supports (for example, commercial carbon black particles, carbon nanotubes, and graphene sheets). The PtSn NPs are highly crystalline with sizes smaller than 2 nm, and they are highly dispersed on the carbon supports with high loadings up to 33 wt %. These characteristics make the as‐synthesized carbon‐supported PtSn NPs more efficient than state of the art commercial Pt/C catalysts applied to the ethanol oxidation reaction (EOR). Significantly enhanced mass catalytic activity (two‐times that of Pt/C) and improved stability are obtained.